Spontaneous Tonsillar Hemorrhage due to Infectious Mononucleosis - Wahba, Andrew (Cureus, 2020)
Spontaneous tonsillar hemorrhage is defined as continuous bleeding for more than one hour, or more than 250 mL of blood loss regardless of the duration of bleeding. It is associated with various pathologic conditions, including acute or chronic tonsillitis, peritonsillar or parapharyngeal abscess, infectious mononucleosis, carotid aneurysm or pseudoaneurysm, and tonsil cancer. It is a rare complication with very limited data reported in the literature. Reported cases indicate an increased incidence in young patients, associated with a higher mortality rate. We report a rare case of spontaneous tonsillar hemorrhage due to infectious mononucleosis in a previously healthy 16-year-old female.